PSX-35 Late-Breaking Abstract: Use of total tract NDF and starch digestibility in beef cow and replacement heifer diet formulation. (30th November 2020) - Dahlke, Garland; Jakub, Devin; Goeser, John; Lundy, Erika L
Abstract: The objective of this trial was to evaluate the effectiveness of using the total tract neutral detergent fiber (TTNDFd) and starch digestibility methodology in the formulation of beef cow and replacement heifer rations. This methodology ultimately applies to the estimation of energy availability to the animal and accompanied performance as outlined by the NASEM 2016 Nutrient Requirements of Beef Cattle publication. Multiparous, Angus cows during the last two months of gestation and yearling replacement, Shorthorn heifers comprised the study. Cows received one of four, dry ingredient diets while heifers received a corn silage-based diet. Feed nutrient evaluation along with intake were documented and applied to the NASEM model for these cattle. Results were compared to actual performance. Acid detergent fiber (ADF) derived energy estimates which generally accompany commercial laboratory feed analysis reports were compared as well. A T-test between actual and projected growth was used to describe the difference. The T-test between the TTNDFd/Starch derived results did not show any statistical difference between the actual and projected results for heifers P(T< =t) 0.15 with an average ADG bias of -0.06 Kg. The cow results over the four diets P(T< =t) ranged from 0.41 to 0.004 with an average bias of 0.04 to 0.27 Kg overestimating ADG. The T-test between the ADF derived results showed a difference between the actual and estimated values for heifers P(T< =t) 0.0004 with an average ADG bias of 0.2 Kg. The cow results over the four diets likewise over estimated available energy substantially. Here the test ranged from P(T< =t) 0.03 to 0.0001 with an average bias of 0.35 to 0.7 Kg. It appears that TTNDFd methodology should be strongly considered in the evaluation of forages and in the development of ration formulation software for beef offered high levels of fiber in their ration.